2023
DOI: 10.1371/journal.pone.0283024
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput newborn screening approach for SCID, SMA, and SCD combining multiplex qPCR and tandem mass spectrometry

Abstract: Early diagnosis of severe combined immunodeficiency (SCID), spinal muscular atrophy (SMA), and sickle cell disease (SCD) improves health outcomes by providing a specific treatment before the onset of symptoms. A high-throughput nucleic acid-based method in newborn screening (NBS) has been shown to be fast and cost-effective in the early detection of these diseases. Screening for SCD has been included in Germany’s NBS Program since Fall 2021 and typically requires high-throughput NBS laboratories to adopt analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Recognizing the need to address the transition from pediatric to adult medicine as the screened population ages, a guideline for transition has also been developed [ 807 ]. A 2022 report provides pilot testing data for a multi-analyte MS/MS procedure that simultaneously detects SCD, BIO, and TYR-I [ 808 ], and a 2023 report provides information on a combination multiplex qPCR and MS/MS procedure for simultaneously detecting SCD, SMA, and SCID [ 809 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recognizing the need to address the transition from pediatric to adult medicine as the screened population ages, a guideline for transition has also been developed [ 807 ]. A 2022 report provides pilot testing data for a multi-analyte MS/MS procedure that simultaneously detects SCD, BIO, and TYR-I [ 808 ], and a 2023 report provides information on a combination multiplex qPCR and MS/MS procedure for simultaneously detecting SCD, SMA, and SCID [ 809 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we were able to implement SMA-NBS without having to charge any additional fees. Tesorero R et al also reported on the scalability and cost-effectiveness of multiplex qPCR assays by integrating screening for sickle cell disease into a pre-existing duplex NBS assay for SCID and SMA [ 38 ]. In addition, as the basis for optional NBS in Osaka had been established by the preceding PID-NBS, the obstetricians in the region had gained a deeper understanding of other treatable target diseases for NBS, including SMA, that should be diagnosed in the neonatal period.…”
Section: Discussionmentioning
confidence: 99%
“…More detailed descriptions about the methods, including measures for quality control, are provided in the supplemental file (section “Method descriptions”) and elsewhere 13 16 .…”
Section: Methodsmentioning
confidence: 99%